Genetic variation along time in a brazilian population of Aedes aegypti (Diptera : Culicidae), detected by changes in the esterase patterns - Sousa-Polezzi, R. D.; Bicudo, HEMD (Springer, 2005)
Aedes aegypti from the Brazilian cities of Sao Jose do Rio Preto (SJ) and Goiania (GO) were analyzed as to their esterase patterns and the results were compared with data obtained about 5 years before for SJ population. Esterase bands not detected in the previous study were now observed in mosquitoes from both SJ and GO populations, being the last considered a population resistant to insecticides. Other similarities between SJ and GO populations in this study, and some differences in comparison with the previous data on SJ were observed, involving, in addition to changes in band type, changes in frequency of mosquitoes expressing them and differential gene activation during development. As it is generally true for genetic features, changes in the esterase patterns are expected to be the result of factors such as selection by environmental conditions and genetic drift. In the present case, continuous use of insecticides aiming mosquito population size control in SJ by sanitary authorities could be involved in the observed changes. Changed esterases were classified as carboxylesterases and cholinesterases, which are enzymes already shown to take part in the development of resistance in several organisms. In addition, data obtained in the elapsed time by authorities responsible for the mosquito control has shown increasing insecticide resistance of SJ population mosquitoes parallel to increase in the total amount of esterases, reinforcing the mentioned possibility.
Keywords: Aedes aegypti; esterase pattern variation; insecticide resistance